Clinical Study of the Snapping Knee in Patients with Rheumatoid Arthritis - OSHIDA Midori; 黒澤 尚; 矢島 一〓; 川上 明; 大沼 正宏; 岸田 由紀子; 薬丸 一洋 (Japanese Journal of Rheumatism and Joint Surgery, 1997)
Following arthroscopy, 11 knees of 6 rheumatoid arthritis (RA) patients were operated on for treatment of snapping knee. Patients ranged in age from 30 to 60 years. Radiographic changes evaluated according to Larsen grade were grade I for 7 knees and grade III for 4 knees. Clinically, the intraarticular nodule was palpable lateral to the inferior aspect of the patella. Snapping occured when the knee was flexed 30-40 degrees. Histologically, the nodule showed typical characteristic features of the RA nodule in 3 knees only, and active rheumatoid synovial mass in 5 knees, while other changes were observed in 3 knees. Arthroscopic findings of synovium in typical RA nodules revealed no inflammation, while the synovial mass cases showed hypertrophic synovial villi.